Sentiment Analysis Of Instagram Social Media Users For BPJS Health Services Using Support Vector Machine Algorithm - Hsb, Dinda Umami; Furqan, Mhd; Armansyah, A (IJISTECH (International Journal of Information System and Technology), 2024)
Health services are an important aspect of people's quality of life, and BPJS as a public health service provider in Indonesia is often the subject of discussion on social media platforms. The SVM method has proven effective in sentiment analysis in various domains, including social media. In this study, data in the form of user comments and uploads on BPJS Instagram accounts were collected and processed to identify Positive, Negative or Neutral sentiments regarding the health services provided by BPJS. with the government's efforts to improve access and quality of health services for pregnant women as well as provide financial protection in order to reduce maternal and infant mortality in Indonesia and has the aim of reducing the burden of childbirth costs for people with low and middle incomes. This information can be input for BPJS in improving quality according to public expectations. In this research with a data set of 600 comments, the research was carried out with the support vector machine classification and the highest accuracy results in the first test experiment on 80% training data and 20% test data with 97% precision, 64% recall and 77% F1-Score obtained accuracy by 83%.